2004
DOI: 10.1103/physrevlett.92.165005
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Multi-keV X-Ray Sources from Ti-Doped Aerogel Targets

Abstract: We have measured the production of hnu approximately 4.7 keV x rays from low-density Ti-doped aerogel (rho approximately 3 mg/cc) targets at the OMEGA laser facility (University of Rochester), with the goal of maximizing x-ray output. Forty OMEGA beams (lambda(L)=0.351 microm) illuminated the two cylindrical faces of the target with a total power that ranged from 7 to 14 TW. The laser fully ionizes the target (n(e)/n(crit) Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 21 publications
0
40
0
Order By: Relevance
“…Laserheated targets typically contain mid-Z elements such as Ti, Fe, V, Ge, or Kr, their K-shell line emission providing 4 to 15 keV x rays. For instance, metal foils 4 , gasfilled targets 5,6 , metal-doped aerogels [7][8][9] , pre-exploded foils 10 , metal oxide nano-fibers 11 , and aerogels attached to foils 12 , can achieve 1 to 10% laser-to-x-ray conversion efficiencies (CE) in a limited energy range. Metal-doped foams can reach high CEs when their density is low enough (< 10 mg/cm 3 ) so that the laser gets absorbed deeper in the target thus volumetrically heating the plasma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laserheated targets typically contain mid-Z elements such as Ti, Fe, V, Ge, or Kr, their K-shell line emission providing 4 to 15 keV x rays. For instance, metal foils 4 , gasfilled targets 5,6 , metal-doped aerogels [7][8][9] , pre-exploded foils 10 , metal oxide nano-fibers 11 , and aerogels attached to foils 12 , can achieve 1 to 10% laser-to-x-ray conversion efficiencies (CE) in a limited energy range. Metal-doped foams can reach high CEs when their density is low enough (< 10 mg/cm 3 ) so that the laser gets absorbed deeper in the target thus volumetrically heating the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Various types of such foams can, in principle, be achieved by tailoring the material composition, density, and pore size. Previous work 7,8 has shown that foams containing various dopants (Ti, Fe, Ge, etc.) could be volumetrically heated when the density is in the range of 5 to 10 mg/cm 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The target design for the current experiments builds on experience at the Nova 29 and Omega 30 laser facilities using modeling and simulation tools that have been validated against experiments [12][13][14][15][16][17][18][19][20][21][22][23][24] . The desired x-ray source characteristics for the present experiments were: a) significant multi-keV x-ray output with energies >3 keV, b) x-ray pulse width of order 5 ns, and c) x-ray rise-time of order 1 ns or longer.…”
Section: A Target Descriptionmentioning
confidence: 99%
“…During the last decade, many research groups have been developing bright, multi-keV x-ray sources [12][13][14][15][16][17][18][19][20][21][22][23][24] . The goal has been to create millimeter-scale, homogeneous, keV-scale-temperature plasmas that are efficient laser-to-x-ray converters.…”
Section: Introductionmentioning
confidence: 99%
“…Lowdensity targets, which allow full volumetric heating of the emitting material by the laser, is one of them. Our group has demonstrated CE's for x-ray energies > 2 keV from 1 to 10 % using pre-exploded foils 2,3 , metal-doped aerogels 4,5 , metal oxide nanofiber 6 , and gas-filled 7,8 targets. Shaped targets, which confine, collect and allow further heating of low-density plasmas ablated from solid target walls, can also substantially increase x-ray conversion efficiency; foil-lined holhraums and halfraums demonstrated CEs of up to 7% 9,10 .…”
Section: Introductionmentioning
confidence: 99%